Analyses of fluorapatite prepared by both chemical precipitation and solid phase reaction methods - Sayenko, S.Yu.; Shkuropatenko, V.А.; Tarasov, R.V.; Prudyvus, K.А.; Savina, S.А.; Zykova, A.V. (Физическая инженерия поверхности, 2013)
At the present study the possibility of obtaining two compositions of Ca₁₀(PO₄)₆F₂ and Ca₉Sr(PO₄)₆F₂
fluoroapatites by both chemical deposition from solutions of the initial components and reaction in the
solid phase was investigated. Using X-ray diffraction (XRD) method was shown that the fluorapatite
synthesis based on calcium pyrophosphate with the addition of strontium takes place at lower temperatures.
Fluoroapatite formation obtained by precipitation process is the result of the reaction between
initial component solutions. At the process of heat treatment of obtained powders by XRD method
was found that compared with fluorapatite obtained by solid phase reaction, fluorapatite obtained by
precipitation method include less content of TCP phase. Maximum density (~92 % of the theoretical
value) is reached for the sample heat treated at 1250 °C with the exposure time up to 6 hours for
fluorapatite obtained by precipitation and at a temperature 1200 °C with the exposure time up to 10
hours for fluorapatite prepared by reaction in the solid phase. данной работе исследовалась возможность получения фторапатита двух составов
Ca₁₀(PO₄)₆F₂ и Ca₉Sr(PO₄)₆F₂ методом химического осаждения растворов исходных компонентов и реакцией в твердой фазе. С помощью рентгенофазового анализа (РФА) показано, что с добавлением стронция синтез фторапатита на основе пирофосфата кальция проходит при более низких температурах. Образование фторапатита, полученного осаждением происходит в результате реакции между растворами исходных компонентов. При термообработке
полученных порошков методом РФА установлено, что по сравнению с фторапатитом, полученным с помощью твердофазной реакции, фторапатит, полученный осаждением содержит меньшее количество ТКФ. Максимальное значение плотности (~92% от теоретической) достигнуто для образцов термообработанных при температуре 1250 °С и времени выдержки 6 часов дляфторапатита, полученного осаждениеми при температуре 1200 °С и времени выдержки 10 часов для фторапатита, полученного реакцией в твердой фазе. У даній роботі досліджувалася можливість отримання фторапатиту двох складів Ca₁₀(PO₄)₆F₂ та Ca₉Sr(PO₄)₆F₂ методом хімічного осадження розчинів вихідних компонентів і реакцією в
твердій фазі. За допомогою рентгенофазового аналізу (РФА) показано, що з додаванням стронцію синтез фторапатиту на основі пірофосфата кальцію проходить при нижчих температурах.
Утворення фторапатиту, отриманого осадження відбувається в результаті реакції міжрозчинами
вихідних компонентів. При термообробці отриманих порошків методом РФА встановлено, що
у порівнянніз фторапатитом, отриманим реакцією в твердій фазі, фторапатит, отриманий осадженням містить меншу кількість ТКФ. Максимальне значення щільності (~92% від теоретичної)
досягнуте для зразків термооброблених при температурі 1250 °С і часі витримки 6 годин для
фторапатиту, отриманого осадженням і при температурі 1200 °С і часі витримки 10 годин для
фторапатиту, отриманого реакцією в твердій фазі.